Behaviour-Based Interviewing : Selecting the Right Person for the Job - L. Fitzwater (Fifty-Minute series., 2004)
Given the pace of technological advances and other workplace changes, it is not enough to hire a person based solely on what you think they can do. Behavioural, objective, fact-based criteria must be developed to increase your change of placing the right person in the right job at the right time. The development of practical, specific, well-defined behavioural criteria will assist you in determining if a candidate can deliver the expected results, as well as help you justify your placement decisions legally. BEHAVIOUR-BASED INTERVIEWING is a highly-interactive book that will give you everything you need to conduct an effective interview and make a successful hiring decision. With checklists and sample forms you will learn how to construct a thorough list of job requirements, prepare for an objective interview, ask the best questions, interpret behaviour, and follow up after an interview, quickly and fairly.